The Relationship between Breast Milk Sufficiency Perceptions and Breastfeeding Self-Efficacy of Mothers with Infants Hospitalized in the NICU: An Analytical Cross-Sectional Study - Nazlı CANDAN; Neriman ÇAĞLAYAN KELEŞ (Archives of Health Science and Research)
Objective: The purpose of this study is to analyze the relationship between perceived breast milk supply and breastfeeding self-efficacy among mothers whose newborns were hospitalized in the neonatal intensive care unit (NICU).